Recombinant linear multiple epitopes of σB protein protect Muscovy ducks against novel duck reovirus infection - Chen, Yiquan; Yan, Zhuanqiang; Liao, Changtao; Song, Yiwei; Zhou, Qi; Shen, Hanqin; Chen, Feng (Frontiers in Veterinary Science, 2024)
Infection by the novel duck reovirus (NDRV) in ducklings causes high mortality, which leads to substantial economic losses in the duck industry in China. To date, no commercial vaccine is available for this disease. In this study, linear B cell epitopes of the σB protein of the NDRV were predicted and recombinant multiple linear B cell epitopes (MLBEs) were constructed through linkers. The recombinant MLBEs were then expressed and purified. One-day-old Muscovy ducklings were immunized with different doses of MLBEs and challenged with 5 × 104 ELD50 of the virulent CHY strain of NDRV 14 days after immunization. The ducklings vaccinated with 20 and 40 μg of MLBE performed no clinical signs or gross or histopathological lesions, indicating 100% protection against infection. The viral load in the liver and spleens of these birds was significantly lower than that in the control group. Additionally, these ducklings exhibited positive seroconversion at 7 days after vaccination on enzyme-linked immunosorbent assay. These results indicate that MLBE of σB could be used as a candidate for developing vaccines against NDRV infection.